2016
DOI: 10.3122/jabfm.2016.03.150280
|View full text |Cite
|
Sign up to set email alerts
|

Building a Foundation to Reduce Health Inequities: Routine Collection of Sociodemographic Data in Primary Care

Abstract: Introduction: Detailed data on social determinants of health can facilitate the identification of inequities in access to health care. We report on a sociodemographic data collection tool used in a family medicine clinic.Methods: Four major health organizations in Toronto collaborated to identify a set of 14 questions that covered a range of social determinants of health. These were translated into 13 languages. This survey was self-administered using an electronic tablet to a convenience sample of 407 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
125
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(131 citation statements)
references
References 67 publications
3
125
0
3
Order By: Relevance
“…Of the 18 studies included in this review, 11 (61.1%) exclusively assessed patients’ perceptions or experiences of the harms associated with the routine collection of sociodemographic data . Four (22.2%) studies exclusively assessed providers’ perceptions of the potential harms for patients from the routine collection of sociodemographic data .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 18 studies included in this review, 11 (61.1%) exclusively assessed patients’ perceptions or experiences of the harms associated with the routine collection of sociodemographic data . Four (22.2%) studies exclusively assessed providers’ perceptions of the potential harms for patients from the routine collection of sociodemographic data .…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were conducted in the USA (66.7%), Canada (27.8%) and the UK (11.1%) . Three studies employed a mixed‐methods design, eight studies used a quantitative design, and the remaining seven used a qualitative design . Three studies included a large variety of racial/ethnic groups including white, black/African American, Latino/Hispanic, Asian and multiracial participants .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of this work, the New Mexico Department of Health now requires managed care organizations to provide community health workers to Medicaid patients. Moving beyond Article, Pinto and his fellow researchers 11 found that asking patients to complete a 14-item survey on SDOHs using a tablet interface was both feasible and acceptable. Developing the survey, garnering staff buy-in, and achieving integration with the clinic's EHR took a significant amount of time.…”
Section: Collecting and Analyzing Sdoh Datamentioning
confidence: 99%